2018
DOI: 10.1016/j.jvs.2018.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Induced DNA Damage in Operators Performing Endovascular Aortic Repair

Abstract: BACKGROUND:Radiation exposure during fluoroscopically guided interventions such as endovascular aortic repair (EVAR) is a growing concern for operators. This study aimed to measure DNA damage/repair markers in operators perfoming EVAR. METHODS:Expression of the DNA damage/repair marker, γ-H2AX and DNA damage response marker, phosphorylated ataxia telangiectasia mutated (pATM), were quantified in circulating lymphocytes in operators during the peri-operative period of endovascular (infrarenal, branched, and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 39 publications
(61 reference statements)
1
29
1
Order By: Relevance
“…Table shows that the OD measured by the leg dosimeter was much higher than for the chest dosimeter, which has been observed before by El‐Sayed et al for aortic repair procedures. Their study also showed that operators without additional leg shielding suffered acute DNA damage, as opposed to the operators equipped with additional leg shielding who did not show any acute DNA damage.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Table shows that the OD measured by the leg dosimeter was much higher than for the chest dosimeter, which has been observed before by El‐Sayed et al for aortic repair procedures. Their study also showed that operators without additional leg shielding suffered acute DNA damage, as opposed to the operators equipped with additional leg shielding who did not show any acute DNA damage.…”
Section: Discussionsupporting
confidence: 70%
“…Their study also showed that operators without additional leg shielding suffered acute DNA damage, as opposed to the operators equipped with additional leg shielding who did not show any acute DNA damage. The leg doses measured by El‐Sayed et al (145 μSv) were in between the leg doses in room B of the current study (91.4 μSv) and the ones in room A (213 μSv). This highlights that also for less complex procedures like diagnostic coronary angiographies, the performing physicians may benefit significantly from additional leg shielding.…”
Section: Discussioncontrasting
confidence: 41%
“…In contrast, 2D-3D registration with an initial DSA makes up for only 0.6% of dose area product. This is of note as major concerns of EVAR comprise occupational contrast and radiation exposure besides durability and rates of re-intervention [6,20,21]. Although radiation exposure is higher with complex EVAR cases (f/bEVAR), radiation protection during standard EVAR is essential since this procedure is more frequent and DNA damage of operators performing complex and standard EVAR cases has been observed [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Radiation exposure on the other hand may put patients and interventionalists at risk [4,5]. Acute radiation-induced DNA damage has been confirmed in operators performing EVAR cases [6]. Hence it seems important to reduce both radiation and contrast exposure during EVAR.…”
Section: Introductionmentioning
confidence: 99%
“…One team investigated DNA damage/ repair markers in operators without leg shielding and found elevated levels of DNA damage markers such as gamma-H2AX and phosphorylated ataxia telangiectasia in circulating lymphocytes. 43 Randomized trials have shown initial mortality benefit in also showed in patients with baseline renal dysfunction or coronary artery disease there was no benefit of EVAR even at first 6 months.…”
Section: Guideline Updates Of Management Of Carotid Artery Diseasementioning
confidence: 99%